Beitrag zum Abflussverhalten seitlich angeströmter Wehranlagen an alpinen Flüssen Am Beispiel gesteuerter Einlaufbauwerke von Hochwasserrückhaltebecken im Nebenschluss - Lindermuth, Adrian (Forum Umwelttechnik und Wasserbau, 2023)
Controlled offline flood retention basins have proven to be a suitable measure to reduce the risk of flooding for downstream areas by means of a targeted capping of the peak discharge. In current flood protection projects they are therefore used on the one hand in case of an extreme event to prevent the failure of existing linear protection measures, and on the other hand with the aim of compensating the increased discharge caused by the implementation of protection measures. The required discharge reduction is achieved by means of controllable inlet structures, which are usually arranged laterally from the channel in the slope area and therefore correspond to side weirs in their design and flow direction. Previous studies have shown that the complex three-dimensional flow behavior and the associated discharge coefficient of these weirs are significantly influenced by a number of geometric and hydraulic parameters.